Utility of recombinant integrin alpha v beta6 as a capture reagent in immunoassays for the diagnosis of foot-and-mouth disease. - Ferris, N; Abrescia, N; Stuart, D; Jackson, T; Burman, A; King, D; Paton, D (2005)
Recombinant integrin alpha v beta6 was evaluated as a capture ligand in a sandwich ELISA for the detection and serotyping of foot-and-mouth disease (FMD) virus. Our routinely applied method employs seven serotype-specific rabbit polyclonal antibodies as capture ligands and seven serotype-specific guinea pig polyclonal antibodies as detecting reagents. The recombinant integrin bound FMD virus of all seven serotypes but not that of another vesicular disease, swine vesicular disease (SVD). Considerable heterotypic cross-reactions were evident when using the integrin capture ligand in combination with guinea pig detecting antibodies but totally type-specific reactions resulted when serotype-specific monoclonal antibodies (mabs) were used instead of the guinea pig reagents. The specificity of reaction of the integrin capture/mab detector combination was superior to that of our routinely employed rabbit/guinea pig ELISA and offers an improvement for test interpretation. As a universal trapping reagent for all FMD virus serotypes the alpha v beta6 recombinant protein also has the potential for application in other test procedures for viral identification (e.g. pen-side chromatographic strip-tests, biosensors, immunocapture RT-PCR, antigenic characterization procedures and monoclonal antibody profiling of emerging field virus strains) and in antibody detection assays employed for the diagnosis of FMD.